The Marketing of poultry meat and eggs in Nairobi. - Ackello-Ogutu, A.C. (University of Nairobi, 1976)
The nature of the problems existing in the poultry meat and egg markets in Nairobi is investigated. Particular emphasis is directed towards revealing the structUre of the retailing and wholesaling systems for both poultry meat and eggs. In addition, sources of supply, marketing channels and functions performed at various levels 1n the marketing of the different products are indicated. Producers and consumers were not interviewed and, hence, the discussion on supply and demand fluctuations and their effect on wholesale and retail prices is based on non-quantitative information provided by the retailers._ Finally the price-setting determinants at wholesale and retail levels are looked into. The term 'poultry' has been adopted and is used synonymously to the term 'chicken'. This is due to the insignificance of other kinds of poultry (e.g. turkeys, duck and geese) in the Nairobi Market. A further distinction Is made within the poultry industry with respect to types of products marketed. Two broad categories of chicken are distingu~shed. These are the 'soft chicken referred to as 'broilers' and thc'tough-meated ones referred to as 'boilers' or 'backyard' Chicken. The types of consumers (private households or' institutions and hotels) and the nature of competition between the 'broiLer pr~ducts ~nd backyard chicken are investigated. Various important aspects forming the background to the study are discussed briefly in Chapter 1. Chapters 2, 3 and 4 are devoted to introductory remarks about the existing problems in the poultry meat and egg markets in Nairobi, objectives of the study and research methodology respectively. The survey results for poultry meat marketing are presented in Chapter 5 and those for egg marketing in Chapter 6. Additional survey results for both pOultry meat and egg marketing appear in Chapter 7. The last chapter (Chapter 8) brings together all the survey,results in a summarized form. Finally, a fe~ recommendations are ~resented at the end of this chapter. NOTE: Tables appearing in Chapters 5, 6 and 8 without any mention of source are from the author's own survey results of 1975/76.